From QAAPAPLE 1 to QAAPAPLE 2: how do we move from one algorithm to another one with Long Acting Antipsychotics (LAIs). (1st December 2020) - Stip, Emmanuel; Grignon, Sylvain; Roy, Marc André; Bloom, David; Osman, Ossama; Amiri, Leena; Abdel Aziz, Karim; Javaid, Syed Fahad; Arnone, Danilo
ABSTRACT: Background: In 2011, the authors published an algorithm summarizing practice guidelines related to the use of long-acting antipsychotics (LAIs) called the Québec Algorithme Antipsychotique à Action Prolongée (QAAPAPLE), and proposed that it be revised every 5–10 years to update it according to most recent scientific knowledge. Therefore, a re-evaluation of the algorithm was conducted to determine which recommendations were still relevant and which needed modification. Methods: The authors conducted a two-fold approach: a review of the literature to include new evidence since 2011 (controlled trials, meta-analyses, and practice guidelines); and a participatory component involving electronic surveys, conferences, encounters with opinion leadres, and patients' representatives. Results: Overall, prescribers tended to make decisions based on personal experience and conversations with colleagues rather than consulting evidence-based guidelines. To test if the algorithm was useful worldwide, it was presented in the United Arab Emirates, where the feedback was in agreement with the algorithm and its limitations. Conclusions: Since its initial publication, the QAAPAPLE algorithm has been updated to guide clinicians on the use of LAIs. The new algorithm has also been assessed outside Canada to test its generalizability worldwide, and indicated its flexibility, efficiency, and user-friendliness in order to guide clinicians on the use of LAIs.